piRNA cluster database: a web resource for piRNA producing loci - Rosenkranz, David (Nucleic Acids Res, 2016)
Piwi proteins and their guiding small RNAs, termed Piwi-interacting (pi-) RNAs, are essential for silencing of transposons in the germline of animals. A substantial fraction of piRNAs originates from genomic loci termed piRNA clusters and sequences encoded in these piRNA clusters determine putative targets for the Piwi/piRNA system. In the past decade, studies of piRNA transcriptomes in different species revealed additional roles for piRNAs beyond transposon silencing, reflecting the astonishing plasticity of the Piwi/piRNA system along different phylogenetic branches. Moreover, piRNA transcriptomes can change drastically during development and vary across different tissues. Since piRNA clusters crucially shape piRNA profiles, analysis of these loci is imperative for a thorough understanding of functional and evolutionary aspects of the piRNA pathway. But despite the ever-growing amount of available piRNA sequence data, we know little about the factors that determine differential regulation of piRNA clusters, nor the evolutionary events that cause their gain or loss. In order to facilitate addressing these subjects, we established a user-friendly piRNA cluster database (http://www.smallrnagroup-mainz.de/piRNAclusterDB.html) that provides comprehensive data on piRNA clusters in multiple species, tissues and developmental stages based on small RNA sequence data deposited at NCBI's Sequence Read Archive (SRA).